2020
DOI: 10.1186/s12960-020-00532-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the recruitment of foreign nurses in Japan: a nationwide study of hospitals

Abstract: Background Nurse migration under bilateral agreements is a recent global trend, although lack of consultation with the health industries has led to challenges in the recruitment of foreign nurses by hospitals. To analyze the prevailing perception of hospitals on the Economic Partnership Agreement (EPA), under which Japan opened the doors to foreign nurses, we surveyed hospitals that are yet to employ foreign nurses. Methods An anonymous questionnaire was developed and distributed to eligible hospitals; it as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…13 However, the opposite case was for Vietnam nurses, as they have higher Japanese language level requirements and more well-prepared language skills. 24 In Indonesia, the Japanese language preparation program only offers the basic skills, while the more advanced skills, including daily conversation and Japanese medical language, are also needed as the vocabularies are different. The Japanese language has a crucial role in getting through the exam.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 However, the opposite case was for Vietnam nurses, as they have higher Japanese language level requirements and more well-prepared language skills. 24 In Indonesia, the Japanese language preparation program only offers the basic skills, while the more advanced skills, including daily conversation and Japanese medical language, are also needed as the vocabularies are different. The Japanese language has a crucial role in getting through the exam.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies revealed that the nurses’ motivation to pass the exam was associated with several factors: effective learning strategies, a comfortable study environment, and support from hospital leadership. 24 , 29 As lack of preparations can cost them licensure, these strategies are intended to minimize the chances of failing the exam. 30 It is suggested that both the Indonesian and Japanese governments provide more training for the candidates, focusing on the Japanese language or exam materials.…”
Section: Discussionmentioning
confidence: 99%
“…Japan is recognized as one of the main destination countries for the migration of health-care workers, attracting nurses from various nations (Efendi et al , 2017; Hirano et al , 2020). However, Japan faces a significant challenge with its aging population, which is the highest globally.…”
Section: Introductionmentioning
confidence: 99%
“…Failure to pass the exam requires them to return to their home country after completing a three-year contract for nurses or a four-year contract for caregivers. Conversely, successful candidates are awarded the “Medical Services” for registered nurses or “Nursing Care” for certified care workers visa (Ministry of Foreign Affairs of Japan, 2023), which can be renewed indefinitely as long as they are engaged in their designated visa jobs (Efendi and Gunawan, 2022; Hirano et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Governments resort to diversified strategies to solve the nursing shortage; one of them is the overseas recruitment of nurses. However, some hospitals' managers do not agree with employing international nurses, believing that they will face communication and interaction problems that will make it difficult for them to adapt to the host country (Hirano et al, 2020). Job opportunities and better social conditions are often the main reasons why nurses decide to work abroad (Rodr ıguez et al, 2014;Keshet and Popper-Giveon, 2016).…”
Section: Introductionmentioning
confidence: 99%